Factors influence customer acceptance towards food biotechnology product / Hafizah Mohd Nor - Mohd Nor, Hafizah (Faculty of Business and Management, 2009)
The purpose of study this study is to define the factors that influence customer acceptance among Malaysian towards food biotechnology product. The collection of information gathered from the secondary data trough the journals local and internationally. From the study, researcher identified three factors arise such Benefits, Trust, and Social Norms. Then, researcher interprets by doing data analysis to achieve the objective of this study. Conclusion, researcher give some suggestion on improve the benefits of food, and implement labeling as important factor in producing food biotechnology.